Zebrafish Erc1b mediates motor innervation and organization of craniofacial muscles in control of jaw movement. Issue 1 (4th July 2022) - Luderman, Lauryn N.; Michaels, Mackenzie T.; Levic, Daniel S.; Knapik, Ela W.
Abstract: Background: Movement of the lower jaw, a common behavior observed among vertebrates, is required for eating and processing food. This movement is controlled by signals sent from the trigeminal motor nerve through neuromuscular junctions (NMJs) to the masticatory muscles. Dysfunctional jaw movements contribute to craniomandibular disorders, yet the pathophysiology of these disorders is not well understood, as limited studies have been conducted on the molecular mechanisms of jaw movement. Results: Using erc1b/kim m533 genetic loss of function mutant, we evaluated lower jaw muscle organization and innervation by the cranial motor nerves in developing zebrafish. Using time‐lapse confocal imaging of the erc1b mutant in a transgenic fluorescent reporter line, we found delayed trigeminal nerve growth and disrupted nerve branching architecture during muscle innervation. By automated 3D image analysis of NMJ distribution, we identified an increased number of small, disorganized NMJ clusters in erc1b mutant larvae compared to WT siblings. Using genetic replacement experiments, we determined the Rab GTPase binding domain of Erc1b is required for cranial motor nerve branching, but not NMJ organization or muscle attachment. Conclusions: We identified Erc1b/ERC1 as a novel component of a genetic pathway contributing to muscle organization, trigeminal nerve outgrowth, and NMJ spatial distribution during development that is required for jaw movement. Key Findings: A craniofacial genetic zebrafish mutant, kimble (kimm533), that carries a loss of function variant in the erc1b gene has jaw movement defects. Erc1b function is required for organization of the lower jaw muscles, including tendon attachments. Erc1b is required for trigemeinal nerve outgrowth, and nerve branching architecture during innervation of the jaw muscles. Erc1b/ERC1 is a novel component of a genetic pathway that is involved in the organization of craniofacial muscle attachments and cranial motor nerve innervation.